Antiproliferative effect of Tualang honey on oral squamous cell carcinoma and osteosarcoma cell lines - Ismail Noorliza M; Khattak Mohammed N; Othman Nor H; Ghashm Abdulmlik A; Saini Rajan (BMC, 2010)
Abstract Background The treatment of oral squamous cell carcinomas (OSCC) and human osteosarcoma (HOS) includes surgery and/or radiotherapy which often lead to reduced quality of life. This study was aimed to study the antiproliferative activity of local honey (Tualang) on OSCC and HOS cell lines. Methods Several concentrations of Tualang honey (1% - 20%) were applied on OSCC and HOS cell lines for 3, 6, 12, 24, 48 and 72 hours. Morphological characteristics were observed under light and fluorescent microscope. Cell viability was assessed using MTT assay and the optical density for absorbance values in each experiment was measured at 570 nm by an ELISA reader. Detection of cellular apoptosis was done using the Annexin V-FITC Apoptosis Detection Kit. Results Morphological appearance showed apoptotic cellular changes like becoming rounded, reduction in cell number, blebbed membrane and apoptotic nuclear changes like nuclear shrinkage, chromatin condensation and fragmented nucleus on OSCC and HOS cell lines. Cell viability assay showed a time and dose-dependent inhibitory effect of honey on both cell lines. The 50% inhibitory concentration (IC50) for OSCC and HOS cell lines was found to be 4% and 3.5% respectively. The maximum inhibition of cell growth of ≥80% was obtained at 15% for both cell lines. Early apoptosis was evident by flow cytometry where percentage of early apoptotic cells increased in dose and time dependent manner. Conclusion Tualang honey showed antiproliferative effect on OSCC and HOS cell lines by inducing early apoptosis.